Skuteczna polityka prorodzinna fundamentem stabilności demograficznej i społeczno-ekonomicznej Polski. Koncepcja rozwiązań systemowych - Żebrok, Przemysław (Kultura-Społeczeństwo-Edukacja, 2025)
Like many European countries, Poland is facing a growing demographic crisis that may soon significantly impact the country’s economic and social stability. Key contributing factors include a persistently low fertility rate, labor migration, and population aging. These phenomena result in reduced human capital, decreased economic competitiveness, and increased pressure on healthcare and pension systems. The article emphasizes the need for a long-term, responsible, and effective pro-family policy as a vital tool for addressing these challenges. The family is recognized as the foundation of demographic resilience, with a particular focus on the role of women as guardians of intangible values and the spiritual dimension of the home. The paper presents an analysis of statistical data and a review of family policy solutions implemented in Poland and selected European countries, offering systemic proposals aimed at boosting fertility and strengthening social capital.